Ranking of persister genes in the same Escherichia coli genetic background demonstrates varying importance of individual persister genes in tolerance to different antibiotics - Wu, Nan; He, Lei; Cui, Peng; Wang, Wenjie; Yuan, Youhua; Liu, Shuang; Xu, Tao; Zhang, Shanshan; Wu, Jing; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2015)
Despite the identification of many genes and pathways involved in the persistence phenomenon of bacteria, the relative importance of these genes in a single organism remains unclear. Here, using Escherichia coli as a model, we generated mutants of 21 known candidate persister genes and compared the relative importance of these mutants in persistence to various antibiotics (ampicillin, gentamicin, norfloxacin, and trimethoprim) at different times. We found that oxyR, dnaK, sucB, relA, rpoS, clpB, mqsR, and recA were prominent persister genes involved in persistence to multiple antibiotics. These genes map to the following pathways: antioxidative defense pathway (oxyR), global regulators (dnaK, clpB, and rpoS), energy production (sucB), stringent response (relA), toxin–antitoxin (TA) module (mqsR), and SOS response (recA). Among the TA modules, the ranking order was mqsR, lon, relE, tisAB, hipA, and dinJ. Intriguingly, rpoS deletion caused a defect in persistence to gentamicin but increased persistence to ampicillin and norfloxacin. Mutants demonstrated dramatic differences in persistence to different antibiotics at different time points: some mutants (oxyR, dnaK, phoU, lon, recA, mqsR, and tisAB) displayed defect in persistence from early time points, while other mutants (relE, smpB, glpD, umuD, and tnaA) showed defect only at later time points. These results indicate that varying hierarchy and importance of persister genes exist and that persister genes can be divided into those involved in shallow persistence and those involved in deep persistence. Our findings suggest that the persistence phenomenon is a dynamic process with different persister genes playing roles of variable significance at different times. These findings have implications for improved understanding of persistence phenomenon and developing new drugs targeting persisters for more effective cure of persistent infections.